2018
DOI: 10.1016/j.eclinm.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance Analysis of the Point-of-Care Bilistick System in Identifying Severe Neonatal Hyperbilirubinemia by a Multi-Country Approach

Abstract: Importance The real prevalence and clinical burden of severe neonatal jaundice are undefined due to difficulties in measuring total serum bilirubin (TSB) outside secondary and tertiary clinical centers. Objective To assess the diagnostic performance of the point-of care Bilistick System (BS) in identifying neonatal jaundice patients requiring treatment. Design Between April 2015 and November 2016, 1911 neonates, were recruited to participate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 31 publications
0
39
1
Order By: Relevance
“…This population contrasts with that of the three previous studies that tested the BS under ideal conditions: in the first study, neonates had a lower mean HCT value of 41.5% 19 , those enrolled in the second study were of an older median age of 6 days with venous blood 20 and in the most recent multi-centre study, the median HCT was 42.7% IQR (38.0-48.0) at a median age of 4 days 21 .…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…This population contrasts with that of the three previous studies that tested the BS under ideal conditions: in the first study, neonates had a lower mean HCT value of 41.5% 19 , those enrolled in the second study were of an older median age of 6 days with venous blood 20 and in the most recent multi-centre study, the median HCT was 42.7% IQR (38.0-48.0) at a median age of 4 days 21 .…”
Section: Discussionmentioning
confidence: 63%
“…The study concluded that BS had comparable accuracy to the TcB JM-103. A recent multi-centre study reported the BS to slightly underestimate SBR value with maximum limits of agreements of −128.3 to 102.6 µmol/l 21 .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…This population contrasts with that of the three previous studies that tested the BS under ideal conditions: in the first study, neonates had a lower mean HCT value of 41.5% 22 , those enrolled in the second study were of an older median age of 6 days with venous blood 23 and in the most recent multi-centre study, the median HCT was 42.7% IQR (38.0-48.0) at a median age of 4 days 24 .…”
Section: Discussionmentioning
confidence: 63%
“…The study concluded that BS had comparable accuracy to the TcB JM-103. A recent multi-centre study reported the BS to slightly underestimate SBR value with maximum limits of agreements of −128.3 to 102.6 µmol/l 24 .…”
Section: Introductionmentioning
confidence: 93%